Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/ijerph14010059
|View full text |Cite
|
Sign up to set email alerts
|

Serum Polychlorinated Biphenyls Increase and Oxidative Stress Decreases with a Protein-Pacing Caloric Restriction Diet in Obese Men and Women

Abstract: The purposes were to compare the effects of a: (1) 12-week P-CR weight loss (WL) diet (Phase 1) between obese men and women and; (2) 52-week modified P-CR (mP-CR) vs. heart healthy (HH) weight maintenance (WM) diet (Phase 2) on serum PCBs and oxidative stress biomarkers (thiobarbituric acid reactive substances, TBARS; total antioxidant capacity, TAC) in 40 obese participants (men, n = 21; women, n = 19). Participants received dietary counseling and monitoring of compliance. PCBs, TBARS, and TAC were assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…The observed increased urinary excretion of lipophilic toxicants is consistent with recent report describing how such a nutritional plan followed by Dr. JB is associated with an increase of serum concentrations of lipophilic pollutants such as polychlorinated biphenyls, possibly mobilized from adipose tissue. (3) We attribute the increased urinary excretion of lipophilic chemicals to the effects of the cleansing procedures associated with the plan described in He et al (3) as well as to the known detoxifying effect of probiotics. For example, Lactobacillus acidophilus, a component of the probiotic yogurt used in this study, is endowed with antioxidant effects, decreasing malondialdehyde and increasing the levels of the antioxidants, glutathione reductase, superoxide dismutase, and glutathione peroxidase.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The observed increased urinary excretion of lipophilic toxicants is consistent with recent report describing how such a nutritional plan followed by Dr. JB is associated with an increase of serum concentrations of lipophilic pollutants such as polychlorinated biphenyls, possibly mobilized from adipose tissue. (3) We attribute the increased urinary excretion of lipophilic chemicals to the effects of the cleansing procedures associated with the plan described in He et al (3) as well as to the known detoxifying effect of probiotics. For example, Lactobacillus acidophilus, a component of the probiotic yogurt used in this study, is endowed with antioxidant effects, decreasing malondialdehyde and increasing the levels of the antioxidants, glutathione reductase, superoxide dismutase, and glutathione peroxidase.…”
Section: Discussionmentioning
confidence: 92%
“…In March 2017, JB embarked on an intermittent fasting program patterned on the weight loss program described by He et al (3) Shortly thereafter, he introduced daily consumption of 100 ml of probiotic yogurt aimed at supporting the immune system and helping detoxification, choosing a product whose properties have been previously described. (8,9) Blood and urine analyses were performed immediately before and after the three-month experience.…”
Section: Subject and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beneficial Lactobacillus strains were believed added by the probiotic yogurt with the ratio of expected/beneficial flora registering a twofold increase for Lactobacillus. These results can be interpreted considering that removal of non-metal toxicants is a well-established feature of probiotics, such as those present in the product consumed by the subject (Blythe et al, 2017;He et al, 2017).…”
Section: Glyphosatementioning
confidence: 88%
“…Additional studies have demonstrated similar results in other obese rodent models [17, 18] . Mechanistic studies in humans are limited, but few have demonstrated these same findings in obese individuals [1921] . It seems these mechanisms of CR also contribute to increased life span, although this aspect is outside the scope of this review.…”
Section: Diet Composition For Obesity and Preventing Excess Weight Gainmentioning
confidence: 99%